The Determinants of the Israeli Strategic Culture = Determinanty izraelskiej kultury strategicznej - Kopeć, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The notion of strategic culture concentrates on intangible aspects that shape foreign and security policies of every state. The article presents the determinants of Israeli strategic culture considering both Israeli geopolitical situation, and the factors modeling its social landscape.
Keywords: strategic culture; security threats; qualitative edge; kultura strategiczna; zagrożenia dla bezpieczeństwa; supremacja jakościowa